Phylogenetic relationships among tribes of the green lacewing subfamily Chrysopinae recovered based on mitochondrial phylogenomics - Yunlan Jiang (Nature Portfolio, 2017)
Abstract Chrysopidae (green lacewings) is the second largest family in Neuroptera, and it includes medium-size lacewings largely recognized by the presence of golden-colored eyes, bright green bodies and delicate wings with dense venation patterns. The subfamily Chrysopinae includes 97% of the species diversity in the family and it is currently divided into four tribes: Ankylopterygini, Belonopterygini, Chrysopini and Leucochrysini. Here we sequenced and annotated the nearly complete mitochondrial genomes of four species of each these tribes: Abachrysa eureka, Italochrysa insignis, Leucochrysa pretiosa, Parankyloteryx sp. We then reconstructed the phylogenetic relationships with estimated divergence times among tribes of Chrysopinae based on the mt genomic data. Our results suggest that Chrysopinae sans Nothancyla verreauxi evolved as two reciprocally monophyletic lineages formed by stem members of the tribes Leucochrysini plus Belonopterygini on one hand, and the stem members of Ankylopterygini plus Chrysopini on the other. Our estimations of divergence times place the diversification of stem Chrysopinae into the extant tribes during the Middle Jurassic to Late Cretaceous. The relatively young ages previously estimated for the green lacewing divergences were probably underestimated due to false inferences of homology between non-sister taxa that are later correctly identified as homoplasy after more taxa are added.